Aspirin for primary prevention in diabetes mellitus: from the calculation of cardiovascular risk and risk/benefit profile to personalised treatment - Santilli, Francesca; Pignatelli, Pasquale; Violi, Francesco; Davì, Giovanni (Thrombosis and Haemostasis, 2015)
Type 2 diabetes mellitus is characterised by persistent thromboxane (TX)-dependent platelet activation, regardless of disease duration. Low-dose aspirin, that induces a permanent inactivation of platelet cyclooxygenase (COX)-1, thus inhibiting TXA2 biosynthesis, should be theoretically considered the drug of choice. The most up-to-date meta-analysis of aspirin prophylaxis in this setting, which includes three trials conducted in patients with diabetes and six other trials in which such patients represent a subgroup within a broader population, reported that aspirin is associated with a non-significant decrease in the risk of vascular events, although the limited amount of available data precludes a precise estimate of the effect size. An increasing body of evidence supports the concept that less-than-expected response to aspirin may underlie mechanisms related to residual platelet hyper-reactivity despite anti-platelet treatment, at least in a fraction of patients. Among the proposed mechanisms, the variable turnover rate of the drug target (platelet COX-1) appears to represent the most convincing determinant of the inter-individual variability in aspirin response. This review intends to develop the idea that the understanding of the determinants of less-than-adequate response to aspirin in certain individuals, although not changing the paradigm of the indication to low-dose aspirin prescription in primary prevention, may help identifying, in terms of easily detectable clinical or biochemical characteristics, individuals who would attain inadequate protection from aspirin, and for whom different strategies should be challenged.
Keywords: Antiplatelet agents; diabetes mellitus; aspirin response; prevention